Search for the B-s(0) -> η′ϕ decay - Aaij, R; Adeva, B; Adinolfi, M; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Jurik, N; et al. (Springer, 2017)
A search for the charmless $B^{0}_{s} → η^{′}φ$ decay is performed using $pp$ collision data collected by the LHCb experiment at centre-of-mass energies of $7$ and $8$ TeV, corresponding to an integrated luminosity of 3 fb$^{-1}$. No signal is observed and upper limits on the $B^{0}_{s} → η^{′}φ$ branching fraction are set to $0.82× 10^{-6}$ at $90%$ and $1.01× 10^{-6}$ at $95%$ confidence level.